The way forward in reconciliation through Indigenously-authored children's literature - Tan Maria; Campbell, Sandy; Quaiattini, Andrea (2018)
Introduction: Improving Indigenous health in Canada means understanding reconciliation as it is presented through an Indigenous lens. Storytelling is a way that many Indigenous peoples pass on history, traditions, knowledge, and wisdom from one generation to another. Truth and Reconciliation content presented in children's fictional works by Indigenous authors can provide an accessible starting point for anyone wishing to build awareness and cultural competence in Indigenous health. This paper is Part 2 of a two-part study addressing residential school experiences and the reconciliation process as they appear in children's books authored by Canadian Indigenous peoples. Methods: The Amazon 100 Bestseller Canadian Indigenous Story Books list was sampled over a seven week period; additional titles were gathered from publishers, academic and public library book lists. Books were screened and we determined their relevance to the 10 Principles of Reconciliation and the 94 Calls to Action, identified themes, and then organized books according to those themes. Results & Discussion: Participants in this session will gain an appreciation for the breadth of Indigenous children's publication in Canada. They will also have access to a thematically-organized list of over 100 fictional works for children and youth, created by Canadian Indigenous authors and/or illustrators. This content can be used to discuss Principles and Calls to Action set out by the Truth and Reconciliation Commission. This is a practical tool that can be used by diverse groups looking for stories that promote awareness, discussion, understanding of residential schools, their legacy, and the way forward. Presented at Rant and Roar / Tempêter et Rugir: 2018 Canadian Health Libraries Association / Association des bibliothèques de la santé du Canada (CHLA/ABSC) Annual Conference, Newfoundland, June 18, 2018.